Emerging digital citizenship regimes postpandemic technopolitical democracies - Calzada, Igor (Emerald Publishing Limited, 2022)
In the context of COVID-19, the production and governance of urban space has experienced a rapid digitalization and datafication, creating new challenges for citizenship. The urban realm is not only the environment where a new standard for digital development is set but also the realm from which rescaling nation-states are pervasively emerging. Emerging Digital Citizenship Regimes: Postpandemic Technopolitical Democracies explores the roles played by digital citizenship in the context of changing geographies of the nation-state in Europe in the aftermath of the global pandemic; and reframes the concept of digital citizenship amid the rescaling of nation-states in Europe by connecting it to the increasing digitalisation of urban environment as a corollary of pandemic. By theorising the concept of citizenship in the digital age through the lens of the evolutionary character of its classical concept or by drawing upon the narratives regarding the democratising potential and risks of the Internet, Emerging Digital Citizenship Regimes explores the complex interaction of social and political variables shaping offline and online civic practices and their intertwined relation to the urban environment, analysing the way it is produced and governed in the COVID-19 new context.